Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 4 - Section 4.2 - Solving Systems of Linear Equations by Substitution - Exercise Set: 15

Answer

x = -2 y = -1

Work Step by Step

2x - 5y = 1 3x + y = -7 to the second equation solve y = -7 - 3x becouse 3x + y - 3x = -7 - 3x minus 3x to both sides y = -7 - 3x Substitude y = -7 -3x to the first equation 2x - 5 ( -7 - 3x ) = 1 2x + 35 + 15x = 1 use the distributive property 17x + 35 = 1 simplify 17x + 35 - 35 = 1 - 35 minus 35 to both sides 17x = -34 $\frac{17x}{17}$ =$\frac{-34}{17}$ divide both sides by 17 x = -2 y = -7 - $3\times(-2)$ substitude x for -2 to y = -7 -3x y = -7 + 6 y = -1
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.